EVALUASI KESESUAIAN LAHAN PROVINSI JAWA TIMUR DALAM UPAYA PENINGKATAN PRODUKTIVITAS KOMODITAS SAYURAN (STUDI KASUS: KENTANG) - Ahmad, Sajidan Wildan; Mardiyah, Siti Isnaini; Wiwoho, Bagus Setiabudi (Jurnal Tanah dan Sumberdaya Lahan, 2025)
The increasing demand for land has resulted in the reduction of potential agricultural land. Land suitability evaluation is an effort that can be made to determine the capacity of land for a particular commodity or crop development through various standardized land use requirements. East Java as a region that supplies vegetable commodities on a national scale still requires various efforts to optimize land use. This research aimed to identify areas that have potential land for cultivating potatoes. This identification was carried out using remote sensing which was then cross-checked with actual potato production data from each region in East Java Province. Based on data processing that had been carried out, in general, East Java is dominated by areas with land suitability classes in class N (not suitable), S3 (marginally suitable), and S2 (quite suitable). Lowland areas are dominated by class N (not suitable) because the land characteristics do not meet the requirements for growing potato plants. Meanwhile, the S3 and S2 classes are spread across the highlands with land units that meet the requirements and characteristics of land for cultivating potatoes. Efforts for classification, conservation, and so on become a unity to optimize and increase potato production in each region.